Direct Costs of Acute Recurrent and Chronic Pancreatitis in Children in the INSPPIRE Registry. Issue 3 (March 2016) - Ting, Jie; Wilson, Leslie; Schwarzenberg, Sarah Jane; Himes, Ryan; Barth, Bradley; Bellin, Melena D.; Durie, Peter R.; Fishman, Douglas S.; Freedman, Steven D.; Gariepy, Cheryl E.; Giefer, Matthew J.; Gonska, Tanja; et al.
ABSTRACT: Objective: To estimate selected direct medical care costs of children with chronic pancreatitis (CP) and acute recurrent pancreatitis (ARP). Methods: We performed a cross-sectional study of data from International Study Group of Pediatric Pancreatitis: In Search for a Cure (INSPPIRE), a multinational registry of children with ARP or CP. We determined health care utilization and estimated costs of hospitalizations, surgical and endoscopic procedures, and medications in our study population. Health care utilization data were obtained from all subjects enrolled in the study, and costs were calculated using national United States costs. Results: We included 224 subjects (median age 12.7 years), 42% of whom had CP. Mean number of hospitalizations, including for surgery and endoscopic retrograde cholangiopancreatography, was 2.3 per person per year, costing an estimated average 38, 755 per person per year. Including outpatient medications, estimated total mean cost was 40, 589 per person per year. Subjects using surgical procedures or endoscopic retrograde cholangiopancreatography incurred mean annual costs of 42, 951 per person and 12, 035 per person, respectively. Estimated annual costs of pancreatic enzyme replacement therapy, diabetic medications, and pain medications were 4114, 1761, and 614 per person, respectively. In an exploratory analysis, patients with the following characteristics appear to accrue higher costs than those without them: more frequent ARP attacks per year, reported constant or episodic pain, family history of pancreatic cancer, and use of pain medication. Conclusions: ARP and CP are uncommon childhood conditions. The severe burden of disease associated with these conditions and their chronicity results in high health care utilization and costs. Interventions that reduce the need for hospitalization could lower costs for these children and their families.